My favourite Prophet Muhammad (S.A.W) stories - Khan, Saniyasnain (UAE : Goodword Books, 2024)
My Favourite Prophet Muhammad (S.A.W) Stories is a beautifully illustrated collection of short, simple, and engaging tales from the life of Prophet Muhammad (S.A.W). Written for young readers, it highlights his kindness, honesty, compassion, and wisdom, teaching moral lessons and Islamic values in an accessible way. Each story is designed to inspire love for the Prophet and encourage good character in everyday life.